Pelaksanaan Pelaksanaan Pembinaan Kemandirian Terhadap Warga Binaan Di Lembaga Pemasyarakatan Kelas II A Pekanbaru: pembinaan kemandirian, warga binaan, lembaga pemasyarakatan - geraldinho; Riky Novarizal (UIR PRESS, 2026)
This study aims to analyze the implementation of inmate self-reliance development programs in correctional institutions. The study used a qualitative approach with data collection techniques through interviews and documentation, which were analyzed using NVivo. The results showed that self-reliance development was carried out through skills training programs adjusted to the needs and potential of inmates. The implementation of the program was supported by collaboration with external parties and supervision from correctional officers. Evaluation was conducted through the assessment of skills and behavioral changes of inmates. The obstacles encountered included differences in inmate characteristics and limited supporting facilities. Self-reliance development had a positive impact on improving skills, behavioral changes, and inmates’ readiness to reintegrate into society after release.